2010
DOI: 10.1080/15732479.2010.539061
|View full text |Cite
|
Sign up to set email alerts
|

Modal parameter identification of short span bridges under a moving vehicle by means of multivariate AR model

Abstract: This study is intended to investigate the feasibility of health monitoring of short span bridges based on modal parameter identification using the vibration data of the bridge induced by a moving vehicle. The idea of this study using the traffic-induced vibration of short span bridges which is a kind of non-stationary process is that the modal parameters identified repeatedly under a given moving vehicle provide a pattern which may provide useful information to decide current health condition of bridges. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 11 publications
(13 reference statements)
0
43
0
Order By: Relevance
“…The Mahalanobis distances of system frequencies and damping constants identified by means of the AR model 14), 16) are summarized in Appendix B for information. Since, in applying MTS, the number of evaluation items has to be unified across all observations, frequencies and damping constants have to be identified at all three observation points without fail.…”
Section: (2) Fault Detectionmentioning
confidence: 99%
“…The Mahalanobis distances of system frequencies and damping constants identified by means of the AR model 14), 16) are summarized in Appendix B for information. Since, in applying MTS, the number of evaluation items has to be unified across all observations, frequencies and damping constants have to be identified at all three observation points without fail.…”
Section: (2) Fault Detectionmentioning
confidence: 99%
“…The fundamental concept of this technology is that modal parameters are functions of structure's physical properties and a change in these physical properties, such as reduced stiffness resulting from damage, will detectably change these modal properties. In identifying modal parameters, many studies also utilize a linear time-series model (Shinozuka et al 1982, He & De Roeck 1997, Carden & Brownjohn 2008, Kim et al 2012. Existing studies show the feasibility of detecting bridge damage from changes in dynamic parameters, focusing on changes of modal frequencies, damping and mode shapes under a controlled condition (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Static variations can be directly related to mass; however, traffic-induced dynamic variation has been shown to be nonlinear and can decrease with an increasing load effect [93]. This further complicates the vibration-based monitoring of in-service bridges, as perceived changes in a bridge's modal parameters may actually be the interaction response of a healthy bridge with a passing vehicle [85]. This relationship is difficult to discern, as it is based on a number of variable factors such as, vehicle weight, velocity, number of vehicles, bridge weight, and temperature.…”
Section: Problematic Effects Of Environmental and Operational Conditionsmentioning
confidence: 99%
“…Kim et al [85] observed that mass variations induced by traffic loading affect shorter span bridges much more than stiffness variations induced by environmental conditions, as shorter span bridges are less susceptible to ambient excitations. In another study, Kim et al [86] demonstrated that natural frequency variations due to traffic loads were almost negligible for middle to long span bridges.…”
Section: Problematic Effects Of Environmental and Operational Conditionsmentioning
confidence: 99%